2011
DOI: 10.5539/jmr.v3n2p157
|View full text |Cite
|
Sign up to set email alerts
|

Using Mathematical Model to Depict the Immune Response to Hepatitis B Virus Infection

Abstract: A simplified mathematical model of immune responds to Hepatitis B Virus (HBV) infection is presented. This focuses on the control of the infection by the interferons, the innate and adaptive immunity. The model was compartmentalized as appropriate and the resulting model equations were solved numerically. A mathematical analysis of the model shows that both disease-free and endemic equilibrium point exist and we derive conditions for their stability. We perform sensitivity analysis on the model parameters, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The simulation analysis shows that at all the stages of immune response to viral infections, the cells of the immune system considered increase as viral load decreases which agrees with the three categories of viral loads of the study of Hancioglu et al (2007). In summary, the stability analysis in the current study is in consistent with the results of Anderson and May (1992), Bittner and Wahl (2000), Wodarz (2004), Hancioglu et al (2007), Wiah et al (2011), Nakata (2011 and Tian and Wang (2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The simulation analysis shows that at all the stages of immune response to viral infections, the cells of the immune system considered increase as viral load decreases which agrees with the three categories of viral loads of the study of Hancioglu et al (2007). In summary, the stability analysis in the current study is in consistent with the results of Anderson and May (1992), Bittner and Wahl (2000), Wodarz (2004), Hancioglu et al (2007), Wiah et al (2011), Nakata (2011 and Tian and Wang (2015).…”
Section: Discussionsupporting
confidence: 88%
“…The categories with their corresponding viral loads also corresponds to the continuous reduction of viral load at the various stages of this current study. The results of the study of Wiah et al (2011) showed the existence of disease free and endemic equilibrium states. The analysis of the adaptive immune response stage of this same study showed that with sufficient antibody response with enough specificity, the dynamics is able to restore the health of the host irrespective of the intensity of the innate response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Type-2 interferons IFN-γ, denoted as F 2 (t), are produced by CTLs and NKs (natural killer cells) N (t) [12,13,35,36] at rates p 2 and p 3 , respectively, and they are lost at a rate δ 2 . Both types of interferons have the capacity to render the uninfected cells protected from infection through making them resistant to infection [19,37,38], or by turning them into refractory cells [18,39]. Therefore, the combined effect of interferons making uninfected cells refractory is taken to be ϕ 1 (F 1 + F 2 ) per uninfected cell, and refractory cells can lose their viral resistance at a rate ρ [20].…”
Section: Model Derivationmentioning
confidence: 99%
“…Application of the mathematical models to different parameters shows that some patients get cleared of the virus quickly due to drug therapy, whereas in case of other patients the drug therapy works much slower [12]. Therefore, in some cases treatment has to be stopped.…”
Section: Introductionmentioning
confidence: 99%